Atuação profissional e participação no desenvolvimento do campo científico em Ciência da Informação: estudo dos egressos do Programa de Pós-Graduação em Ciência da Informação da UFMG, 1992-2005 - Joefisson Saldanha dos Santos (2006)
It investigates the professional participation and its contributions to the scientific field of Information Science both run by researchers from Programa de Pós-graduação em Ciência da Informação da UFMG (PPGCI/UFMG). Such students defended their thesis/dissertations between 1992-2005. The research adopted both the qualitative and the quantitative modality right due to come closer to the object. A questionnaire has been sent to the whole research group formed by 183 researchers (masters and doctors) who defended their thesis/dissertation over the period mentioned above. The questionnaires answering rated 24,6% of the total, which means that 45 (forty-five) questionnaires had been answered. Four professors heading the Program were interviewed in the same period (1992-2005) in order to come out with the perspective of analysis used by the Institutional view concerning graduate students. Documentary Studies had been done due to rate the researchers participation in the publishing of articles in the main Information Sciences magazines all over the country. Another study stood for an analysis on the origins of ENANCIBs (I to VI) and also on the Lattes Platform, both studies aiming to check the rate of graduate students with their curricula in that CNPqs base. A large variety had been found in what concerns the graduate students academic course seen in the sample (45 questionnaires). The highest percentages were at: Library Science, 22,2%; Engineering, 15,5%; Psychology, 8,9%; Computer Science, 6,7% and History, 6,7%. However, if the object analysed is the graduation of graduate students as in its whole (183 researchers), the most remarkable courses, then, were: Library Science, 19,7%; Engineering, 11,5%; Management, 10,4%; Computer Science, 10,4% and Communication, 9,8%. As far as it concerns the participation of graduate students in the field of Information Science before joining PPGCI/UFMG, 73% of them said they were already familiar with the field. From the perspective of professional participation, the research showed the existence of a higher concentration of researchers right after obtaining either a master or a doctors degree. On the other hand, the percentages of participation were too low when the analysis made was on the contributions given to develop the scientific field of Information Science. The documentary study made sure of graduate students insufficient participation for the development of the field. However, if the percentages concerning the advance of the scientific field are not in agreement with what has been expected by the Institutional view, it has been growing relatively yearly.